Non-target Site Herbicide Resistance Is Conferred by Two Distinct Mechanisms in Black-Grass (Alopecurus myosuroides) - Franco-Ortega, Sara; Goldberg-Cavalleri, Alina; Walker, Andrew; Brazier-Hicks, Melissa; Onkokesung, Nawaporn; Edwards, Robert (Frontiers in Plant Science, 2021)
Non-target site resistance (NTSR) to herbicides in black-grass (Alopecurus myosuroides) results in enhanced tolerance to multiple chemistries and is wide-spread in Northern Europe. To help define the underpinning mechanisms of resistance, global transcriptome and biochemical analysis has been used to phenotype three NTSR black-grass populations. These comprised NTSR1 black-grass from the classic Peldon field population which shows broad ranging resistance to post-emergence herbicides, NTSR2 derived from herbicide sensitive (HS) plants repeatedly selected for tolerance to pendimethalin and NTSR3 selected from HS plants for resistance to fenoxaprop-P-ethyl. NTSR in weeds is commonly associated with enhanced herbicide metabolism catalyzed by glutathione transferases (GSTs) and cytochromes P450 (CYPs). As such, the NTSR populations were assessed for their ability to detoxify chlortoluron which is detoxified by CYPs and fenoxaprop, which is acted on by GSTs. As compared with HS plants, enhanced metabolism toward both herbicides was determined in the NTSR1 and NTSR2 populations. In contrast, NTSR3 plants showed no increased detoxification capacity, demonstrating that resistance in this population was not due to enhanced metabolism. All resistant populations showed increased levels of AmGSTF1, a protein functionally linked to NTSR and enhanced herbicide metabolism. Enhanced AmGSTF1 was associated with increased levels of the associated transcripts in NTSR1 and NTSR2 plants, but not in NTSR3, suggestive of both pre- and post-transcriptional regulation. The related HS, NTSR2 and NTSR3 plants were subject to global transcriptome sequencing and weighted-gene co-expression network analysis to identify modules of genes with coupled and regulatory functions. In the NTSR2 plants, modules linked to detoxification were identified, with many similarities to the transcriptome of NTSR1 black-grass. Critical detoxification genes included members of the CYP81A family and tau and phi class GSTs. The NTSR2 transcriptome also showed network similarities to multiple drug resistance in man. In contrast, completely different gene networks were activated in the NTSR3 plants, showing the greater similarity to the responses to cold and osmotic shock and fungal infection determined in cereals. Our results demonstrate that NTSR in black-grass can arise from at least two distinct mechanisms, each involving complex changes in gene regulatory networks.